Patient Perspectives Regarding Ethics of Spinal Column Stimulators in the Surgical Management of Persistent Postoperative Neuropathic Pain. Issue 3 (5th August 2016) - Samuel, Nardin; Bernstein, Mark; Alotaibi, Naif M.; Kalia, Suneil K.; Shamji, Mohammed F.
Abstract : Objective: The aim of this study is to better understand perspectives of patients with persistent postoperative neuropathic pain (PPNP) and assess perceptions of the ethical issues surrounding their structural spinal surgeon also performing spinal cord stimulation (SCS). Methods: Semistructured face‐to‐face interviews with 20 neurosurgical spine patients were conducted. Patients were recruited from the neurosurgery clinics at Toronto Western Hospital and were seen in consultation for PPNP. Interviews were transcribed and subjected to thematic analysis using open and axial coding. Results: The range of the duration of participants' preoperative symptoms varied from one month to more than 20 years, and was primarily back dominant (13/20). The median time since patients most recently underwent spinal surgery was three years. The majority of patients (15/20) do not view their current condition of PPNP as a failure of their initial spine surgeon. The most commonly reported reason for this is that patients trusted their physician and clear communication between the physician and the patient, prior to their surgery, ensured an understanding of the goals of the procedure. Nearly unanimously (19/20), patients did not perceive an ethical problem with a surgeon performing a structurally corrective spinal surgery and subsequently also implanting a SCS device if the same patient that develops medically refractory PPNP. Conclusions: This is the first clinical qualitative study of values and ethical perceptions of patients with medically refractory PPNP. Our findings provide a framework for understanding the values of patients with PPNP and demonstrate that a strong surgeon‐patient relationship can ameliorate concerns surrounding PPNP and SCS implantation.